2015
DOI: 10.1016/j.scr.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase serum amyloid A induces proinflammatory cytokines and mineralization via toll-like receptor 4 in mesenchymal stem cells

Abstract: The role of serum amyloid A (SAA) proteins, which are ligands for toll-like receptors, was analyzed in human bone marrow-derived mesenchymal stem cells (hMSCs) and their osteogenic offspring with a focus on senescence, differentiation and mineralization. In vitro aged hMSC developed a senescence-associated secretory phenotype (SASP), resulting in enhanced SAA1/2, TLR2/4 and proinflammatory cytokine (IL6, IL8, IL1β, CXCL1, CXCL2) expression before entering replicative senescence. Recombinant human SAA1 (rhSAA1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 45 publications
4
43
0
4
Order By: Relevance
“…In a recent study by Ebert et al . 46 , SAA1 was shown to stimulate a pro-inflammatory phenotype via TLR4 in mesenchymal stem cells by activation of p38 and NFκB pathways, which was believed to be part of the early phase of osteogenic differentiation and the development of senescence. Here we demonstrated that similar signaling pathways underpinned the actions of SAA1 in human amnion fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Ebert et al . 46 , SAA1 was shown to stimulate a pro-inflammatory phenotype via TLR4 in mesenchymal stem cells by activation of p38 and NFκB pathways, which was believed to be part of the early phase of osteogenic differentiation and the development of senescence. Here we demonstrated that similar signaling pathways underpinned the actions of SAA1 in human amnion fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…A list of genes (selected by the authors using educated guesses) that are upregulated after respective time points is provided in Table 1; complete lists can be found in the article. Interestingly, the early genes such as proinflammatory cytokines IL-1b, IL-6, IL-8, the toll-like receptor 4 (TLR4) ligands serum amyloid A1 (SAA1) and SAA2, CYR61/CCN1, connective tissue growth factor (CTGF/CCN2), angiopoietin-like 4 (ANGPTL4) and ANGPTL2 very closely resemble genes that are also relevant in the initial phase of osteogenic differentiation and contribute to angiogenesis in fracture healing [91][92][93]. Already after 2h, the mRNAs encoding proinflammatory genes have gone back to basal levels.…”
Section: Muscle Secretory Products With Endocrine Functionsmentioning
confidence: 99%
“…Many of these genes have putative functions in bone regeneration (see also text). Virtually all genes of the inflammatory phase have implications in the early phase of skeletal stem cell commitment and bone regeneration; also, genes active in neoangiogenesis are relevant for bone healing, regeneration, and remodeling [82,91,96,97]. Abbreviations: CYR61/CCN1: cysteine-rich angiogenic inducer 61, TNF: tumor necrosis factor.…”
Section: Muscle Secretory Products With Endocrine Functionsmentioning
confidence: 99%
See 2 more Smart Citations